MENINGKATKAN PRESTASI BELAJAR MATERI ASKING FOR AND GIVING OPINION MELALUI METODE DISCOVERY LEARNING DI KELAS XI IPA 2 SMAN 6 TAMBUN SELATAN - INDRAWATI INDRAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This Study is aimed to improve learning achievement of students of XI science 2 SMAN 6 Tambun Selatan Bekasi. Students’ learning achievement in “Asking for and Giving Opinion” material is relatively still low. This can be seen from the result of Pretest of the students who obtained classicallly completion scores as many as 15 students or 35.7% of students managed to achieve KKM and 27 students or 64.28% had not reached the completion target. The Study of the usage of Discovery Learning Method in order to improve learning achievement of “Asking for and Giving Opinion” material has been applied on Students of XI science 2 SMAN 6 Tambung Selatan in 2019/2020. This study is a Class Action Research model of Kemmis and Targgart consist of 2 cycles. Data collection technique used observation, documentation and tests. Analysis data used is descriptive quantitative. There was an increased result in students’ learning achievement both in cycle I and II after using Discovery Learning Method. The number students who got KKM in cycle I is 28 students and in cycle II is 42 students. The percentage of classical completion in cycle I is 66.66% and in cycle II is 100%. The result of this study is that the use of Discovery Learning method in the material “Asking for and Giving Opinion” can improve the learning achievemnt of students XI science 2 SMAN 6 Tambun Selatan. ABSTRAKPenelitian ini bertujuan untuk meningkatan prestasi belajar siswa XI IPA 2 SMAN 6 Tambun Selatan Kab. Bekasi. Prestasi belajar siswa pada materi “asking for and giving opinion” tergolong rendah. Hal ini terlihat dari hasil pretest siswa diperoleh nilai ketuntasan klasikal sebanyak 15 siswa atau 35,7 % siswa berhasil mencapai nilai KKM dan 27 siswa atau 64,28% belum mencapai target ketuntasan. Penelitian tentang penggunaan metode Discovery Learning untuk meningkatkan prestasi belajar materi “asking for and giving opinion” telah dilakukan pada siswa XI IPA 2 SMAN 6 Tambun Selatan tahun ajaran 2019/2020. Penelitian ini merupakan penelitian Tindakan kelas model Kemmis dan Targgart yang terdiri dari 2 siklus. Teknik pengumpulan data menggunakan observasi, dokumentasi dan tes. Analisis data yang digunakan adalah deskriptif kuantitatif. Baik pada siklus I dan siklus II terjadi peningkatan prestasi belajar siswa setelah penggunaan metode Discovery Learning. Jumlah siswa tuntas dari siklus I yaitu 28 siswa dan siklus II 42 siswa. Dengan persentase ketuntasan klasikal pada siklus I yaitu 66,66% dan siklus II 100%. Hasil penelitian ini yaitu penggunaan metode Discovery Learning pada materi “asking for and giving opinion” dapat meningkatkan prestasi belajar siswa XI IPA 2 SMAN 6 Tambun Selatan.